Techniques of Speech Compression in Simultaneous Interpretation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Simultaneous interpretation (SI) requires interpreters to process and convey information in real time while maintaining accuracy and coherence. Due to time constraints and cognitive load, interpreters frequently employ speech compression techniques to ensure efficient and intelligible message delivery. Speech compression in SI involves various linguistic and cognitive strategies, including syntactic restructuring, lexical substitution, omission of redundant elements, summarization, and condensation. These techniques allow interpreters to retain essential meaning while adapting the message to time limitations and linguistic differences between source and target languages. This paper explores the primary speech compression techniques used in simultaneous interpretation, focusing on their effectiveness in different language pairs and interpreting contexts. The study analyzes linguistic transformations and cognitive processing mechanisms that enable interpreters to manage time pressure without distorting the intended message. Additionally, the paper discusses challenges associated with speech compression, such as potential loss of nuance and interpreter fatigue, and suggests training methodologies to enhance compression skills. Understanding and mastering these techniques is crucial for interpreters to maintain fidelity, clarity, and fluency in real-time communication.